PEMANFAATAN LIGNIN KRAFT DARI LINDI HITAM SEBAGAI PEREKAT KAYU KOMPOSIT - Adi Santoso (Universitas Nusa Bangsa, 2011)
Utilization of Kraft Lignin from black liquor as adhesives in the wood composite. The lignin in the sulphate black liquor (known as kraft lignin) has a strong affinity when being reacted with formaldehyde to form lignin formaldehyde adhesives. To increase the bonding strength, the lignin is co-polymerized with phenol or resorcinol to form lignin phenol formaldehyde or lignin resorcinol formaldehyde resins. The resins can be applied in of reconstituted wood products manufacturing such as plywood, finger-jointed wood assembly and glue laminated lumber. The research result showed that each type of lignin based adhesives had specific characters which met Indonesian standard. The test result on plywood which glued by lignin formaldehyde (LF) and lignin phenol formaldehyde (LPF) indicated that bonding strength of the products were 8.0-27.0 kg/cm2, for a while on laminated wood which glued by lignin resorcinol formaldehyde (LRF) indicated that bonding strength of the products were 36.9-88.0 kg/cm2, modulus of rupture and modulus of elasticity was 372-637kg/cm2 and47,164-60,237 kg/cm2, respectively. The formaldehyde emissions were about 0.05-0.14 mg/L. The efficiency of lignin based adhesives on finger joint application reach at 35.4-73.6%. Therefore, the synthesis of lignin based adhesives, an unique wood adhesive with good resin characteristics and met bonding strength and formaldehyde emission requirement as stated in Japanese standard. Keywords : Kraft lignin, composite wood, adhesives ABSTRAK Lignin dalam lindi hitam (dikenal sebagai lignin kraft) memiliki afinitas yang kuat bila direaksikan dengan formaldehida membentuk perekat lignin formaldehida. Guna meningkatkan daya rekatnya, lignin dikopolimerisasi dengan phenol atau resorsinol sehingga terbentuk resin lignin phenol formaldehida atau lignin resorsinol formaldehida. Resin tersebut dapat diaplikasikan dalam pembuatan produk kayu rekonstitusi seperti kayu lapis, papan sambung dan kayu lamina. Hasil penelitian menunjukkan bahwa setiap jenis perekat berbasis lignin memiliki karakter yang spesifik yang memenuhi persyaratan standar Indonesia. Hasil pengujian terhadap kayu lapis yang direkat dengan lignin formaldehida (LF) dan lignin phenol formaldehida (LPF) menunjukkan bahwa keteguhan rekat produk tersebut berkisar antara 8,0-27,0 kg/cm2, sementara untuk kayu lamina yang direkat dengan lignin resorsinol formaldehida (LRF) berkisar antara 36,9-88,0 kg/cm2, dengan modulus of rupture dan modulus of elasticity berturut-turut sekitar 372 - 637kg/cm2 dan47,164 - 60,237 kg/cm2. Emisi formaldehida produk berkisar antara 0,05-0,14 mg/L. Efisiensi perekat berbasis lignin pada aplikasi papan sambung mencapai 35,4 - 73,6%. Produk yang menggunakan perekat berbasis lignin ini memenuhi persyaratan Jepang.Kata kunci : Lignin Kraft, kayu majemuk, perekat